Implementasi Pola Asuh Ayah Tunggal dan Dampaknya terhadap Kemandirian Anak Usia Dini - Adi Saputra; Dadan Nugraha; Purwati Purwati; Fauziyah Syarifatul Huriyah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Early childhood independence is a vital aspect of character development and readiness to face life’s challenges. This study aims to examine the parenting practices of single fathers and their impact on fostering independence in early childhood using a descriptive-analytical literature review approach. The findings reveal that the democratic parenting style is the most effective in promoting independence, characterized by responsibility-sharing, freedom of expression, and open communication. This style supports children’s physical, emotional, social, and moral development. Despite facing challenges such as limited time, advanced age, and dual household roles, single fathers can still provide nurturing and supportive parenting. Contributing factors such as role modeling, emotional support, a conducive environment, and school collaboration further enhance the effectiveness of parenting. The study concludes that the success of fostering independence in single-father families is strongly influenced by the quality of parenting and synergy between family and social environments.